Analisis Spasial Dan Temporal Ruang Terbuka Hijau Di Kota Palu - Ade Prasetya Saputra; Hamzari Hamzari; Sri Ningsih Mallombasang (Universitas Tadulako, 2015)
Green open space ( RTH ) city from year to year has declined significantly , resulting in wide open space from year to year is narrowed . The purpose of this study was to identify available of green space in the city of Palu , to know necessity of green space based on width area and number of population in palu, and to formulate the direction of green space developing in Palu. The Methods that used in this research is Maximum Likelihood Classification (MLC) methods. The image that used was captured from landsat TM 7 year 2009 and 2013. Both processed with Arc GIS 10 and ER Mapper 12 software. The result from five category of land use/cover during 2009 and 2013 is built area increased 36 %, open land increase 74 %, Agricultural green space increase 10 %, other green space decrease 22 %, and water body decrease 40 %. Green open space in Palu needs to develop new concept of green open space, plant tree species that can absorb polution, formulate the direction of green open spaces developing, and make a rule of law about how to manage green open space developing in Palu City.